Aggressive Angiomyxoma: Imaging Findings in 3 Cases With Clinicopathological Correlation and Review of the Literature. Issue 6 (November 2015) - Miguez Gonzalez, Javier; Dominguez Oronoz, Rosa; Lozano Arranz, Pilar; Calaf Forn, Francesc; Barrios Sanchez, Pedro; Garcia Jimenez, Angel
Abstract : Abstract: Aggressive angiomyxoma is a rare mesenchymal tumor with a typical presentation as a slowly growing perineal soft tissue mass in paravulvar and pararectal region in young adult women. We present 3 cases of aggressive angiomyxoma with clinicopathological correlation and describe their main imaging features with emphasis on magnetic resonance imaging, adding useful information about their behavior on dynamic contrast-enhanced sequences and diffusion-weighted imaging and including a comprehensive review of the existing literature.